A history of Russian literature - Kahn, Andrew; Lipovetsky, Mark; Reyfman, Irina; Sandler, Stephanie (Oxford University Press, 2018)
Russia possesses one of the richest and most admired literatures of Europe, reaching back to the eleventh century. This volume provides a comprehensive account of Russian writing from its earliest origins in the monastic works of Kiev up to the present day, still rife with the creative experiments of post-Soviet literary life.